The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.trd.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Detailed assessment of global transport-energy models’ structures and projections

Abstract: This paper focuses on comparing the frameworks and projections from four global transportation models with considerable technology details. We analyze and compare the modeling frameworks, underlying data, assumptions, intermediate parameters, and projections to identify the sources of divergence or consistency, as well as key knowledge gaps. We find that there are significant differences in the base-year data and key parameters for future projections, especially for developing countries. These include passenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 24 publications
6
51
0
Order By: Relevance
“…Historical trends and the baseline year often serve as references to develop future projections. However, the assumption of baseline year data can significantly differ between studies and can lead to different conclusions as found by Yeh et al (2017) [59]. Furthermore, a sensitivity analysis cannot quantify the uncertainty caused by random errors in the input data [49].…”
Section: Limitations Of a Deterministic Uncertainty Analysismentioning
confidence: 98%
“…Historical trends and the baseline year often serve as references to develop future projections. However, the assumption of baseline year data can significantly differ between studies and can lead to different conclusions as found by Yeh et al (2017) [59]. Furthermore, a sensitivity analysis cannot quantify the uncertainty caused by random errors in the input data [49].…”
Section: Limitations Of a Deterministic Uncertainty Analysismentioning
confidence: 98%
“…Annually, HDTs move 60% of the worldwide on-road freight demand, yet they represent only 7-9% of the global vehicle population [2], [3].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Finally, the third transport comparison paper makes the link between integrated assessment models and transport sector-only models (Yeh et al, 2017). In this paper the modelling frameworks, underlying data, assumptions intermediate results, and projections are compared.…”
Section: Model Comparison Studiesmentioning
confidence: 99%